Tillage systems of irrigated rice and compaction of a Planosol - Pedrotti, Alceu; Pauletto, Eloy Antonio; Gomes, Algenor da Silva; Turatti, Ariovaldo Luis; Crestana, Silvio (Pesquisa Agropecuaria Brasileira, 2001)
In 1993, it was evaluated the compaction of a Planosol (Albaqualf) submitted to different tillage systems, measuring soil density through the volumetric ring method, in three layers. Treatments consisted of six tillage systems selected from an experiment conducted at Embrapa-Centro de Pesquisa Agropecuária de Clima Temperado, Pelotas, RS, Brazil, since 1985. High soil density values were obtained; in the first layer (0-10 cm), the no-tillage rice cultivation on the rye-grass straw was the system with the lowest value. The systems that involved more soil mobilization (rice continuous and rotation rice-soybeans-maize) resulted in higher soil density values compared to the reduced preparing systems (rye-grass x rice in zero tillage and soybean x rice in zero tillage). Compacted structures were identified in the intermediate layer (10-20 cm) in all tillage systems, except for the rotation rice-soybean-maize, where soil density differences were not detected among soil layers.